Continuum Robot With Follow-the-Leader Motion for Endoscopic Third Ventriculostomy and Tumor Biopsy - Gao, Yuanqian; Takagi, Kiyoshi; Kato, Takahisa; Shono, Naoyuki; Hata, Nobuhiko (IEEE transactions on biomedical engineering, 2020)
Background: In a combined endoscopic third ventriculostomy (ETV) and endoscopic tumor biopsy (ETB) procedure, an optimal tool trajectory is mandatory to minimize trauma to surrounding cerebral tissue. Objective: This paper presents wire-driven multi-section robot with pushpull wire. The robot is tested to attain follow-the-leader (FTL) motion to place surgical instruments through narrow passages while minimizing the trauma to tissues. Methods: A wire-driven continuum robot with six sub-sections was developed and its kinematic model was proposed to achieve FTL motion. An accuracy test to assess the robot's ability to attain FTL motion along a set of elementary curved trajectory was performed. We also used hydrocephalus ventricular model created from human subject data to generate five ETV/ETB trajectories and conducted a study assessing the accuracy of the FTL motion along these clinically desirable trajectories. Results: In the test with elementary curved paths, the maximal deviation of the robot was increased from 0.47 mm at 30° turn to 1.78 mm at 180° in a simple C-shaped curve. S-shaped FTL motion had lesser deviation ranging from 0.16 to 0.18 mm. In the phantom study, the greatest tip deviation was 1.45 mm, and the greatest path deviation was 1.23 mm. Conclusion: We present the application of a continuum robot with FTL motion to perform a combined ETV/ETB procedure. The validation study using human subject data indicated that the accuracy of FTL motion is relatively high. The study indicated that FTL motion may be useful tool for combined ETV and ETB.